2019
DOI: 10.1111/hdi.12787
|View full text |Cite
|
Sign up to set email alerts
|

Role of type 2 diabetes and hemodialysis in serum adipolin concentrations: A preliminary study

Abstract: Introduction Adipocytokines play a major role in obesity‐associated disorders like insulin resistance (IR). IR is prevalent in diabetes and advanced kidney failure. Adipolin is an adipocytokine with major beneficial effects on insulin sensitivity. This study aimed to investigate adipolin concentration and its relationship with IR and other cardiovascular risk factors in patients with diabetes and/or hemodialysis. Methods In this preliminary study, 24 obese patients with type 2 diabetes (DM) and 30 with hemodia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…Serum adipolin levels in the present study were similar to those in some studies [14] and different from others [28]. The reason for this difference may be due to the influence of various factors, such as demographic differences, different conditions, underlying diseases, kit calibration, and other underlying disease-related factors.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Serum adipolin levels in the present study were similar to those in some studies [14] and different from others [28]. The reason for this difference may be due to the influence of various factors, such as demographic differences, different conditions, underlying diseases, kit calibration, and other underlying disease-related factors.…”
Section: Discussionsupporting
confidence: 81%
“…The anti-atherosclerotic effects of adiponectin have been shown in many studies through various mechanisms, such as inhibition of adhesion of monocytes to the endothelial cells, foam cell formation of macrophages, and proliferation of vascular smooth muscle cells [26, 27]. Alipoor et al [28] also demonstrated the protective effects of adipolin on vascular remodeling by reducing the macrophage inflammatory response. Since this is the first study to indicate a link between CK-MB and CAD severity based on the Gensini score with serum adipolin levels, the precise mechanism of this association is unclear and needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…Adipolin was negatively associated with BMI and HOMA-IR, positively associated with adiponectin and HDL-C in these patients. (17,41,42) In our study, significantly decreased adipolin levels were observed in OB, MO and MetS groups in comparison to N-BMI group.…”
Section: Discussionsupporting
confidence: 58%
“…It exhibits anti-inflammatory effects. (16,17) Adropin is introduced as a fat-burning hormone with multiple functions. It also exhibits positive correlation with adiponectin.…”
Section: Introductionmentioning
confidence: 99%
“…The adipokines analyzed in this study-adipolin, chemerin, and neprilysin-were chosen due to their impact on tissue metabolism and insulin sensitivity [3,4]. Their mechanisms of action are not fully understood, and the results of studies determining the relationships between their blood concentrations and anthropometric and metabolic parameters in humans are inconclusive.…”
Section: Introductionmentioning
confidence: 99%